γδ T cells in hematological malignancies: mechanisms and therapeutic strategies - Xingchi Chen; Guangyu Sun; Xiaoyu Zhu (Blood Science)
γδ T cells are a unique subset of lymphocytes with both innate and adaptive features. They recognize and eradicate various hematological malignancies through different mechanisms, employing factors including γδ TCR, NKR, NKG2D, TRAIL, and perforin/granzyme. They also modulate other immune cells to enhance their antitumor activity. Moreover, γδ T cells have potent antiviral functions after hematopoietic stem cell transplantation (HSCT), which may improve the outcome of patients with hematological malignancies. In this review, we summarize the current knowledge on γδ T cell biology and function in hematological malignancies and HSCT complications. We also discuss the challenges and limitations of the clinical application of γδ T cells, such as their low frequency in peripheral blood and heterogeneity among different subsets. We then highlight some promising strategies for γδ T cell-based therapy, such as using agonist antibodies, cell engagers, or genetic modification technology. Furthermore, we review the recent clinical trials evaluating the safety and efficacy of γδ T-cell therapy in different hematological malignancies. In conclusion, γδ T cells represent a promising immunotherapeutic tool for hematological malignancies that deserves further exploration.